Effect of the support material of IrRu catalysts on CO-assisted NOx reduction - Arshad, Malik Waqar; You, Young Woo; Kim, Young Jin; Heo, Iljeong; Kim, Seok Ki (Chemical Engineering Journal, 2023)
Aluminum oxide (Al2O3)- and titanium dioxide (TiO2)-supported iridium–ruthenium (IrRu) catalysts were synthesized and the effect that their metal particle size and metal–support interactions have on their catalytic performance toward carbon monoxide (CO)-assisted nitric oxide (NO) reduction was investigated. A series of spectroscopic analyses revealed that IrRu bimetallic particles were well-alloyed on both the Al2O3 and TiO2 supports, but that the latter exhibited a smaller size due to the strong interactions between the metal and support. Despite the large metal particle size of IrRu/Al2O3, the selective conversion of NOx to N2 assisted by of CO oxidation was more efficient than that of IrRu/TiO2. Mechanistic and microkinetics analyses suggested that the defect-free flat surface structure of the IrRu alloy was beneficial for selective NOx reduction and CO oxidation due to the moderate binding strength of the intermediates of desired reactions. The metal–support interfaces were found to be inactive regardless of their interaction strength. This analysis provides an explanation for the superior performance of IrRu/Al2O3 compared to its TiO2-supported counterpart due to its few defects, large metal size, and small proportion of metal–support interfaces.
Keywords: % reductions; Carbon monoxide oxidation; Metal particle; Metal-support interfaces; Nitric oxide reduction; Particles sizes; Ruthenium catalysts; Strong metal-support interaction; Structure sensitivity; CO oxidation; NO reduction; Selective catalytic reduction; strong metal-support interaction (SMSI); Structure sensitivity